Death and dying views of the institutionalized elderly. - Tan, Janelle Rose D.
This is a phenomenological study which sought to describe the views on death and dying of the institutionalized elderly, with focus on three aspects, personal meanings of death, fear of death and views of dying process. The participants of this study were four (4) elderly residing in Asilo de Molo. An interview guide was constructed to cull narratives of death an dying from the participants., The results showed that the personal meanings of participants are generally similar. These are views of death using a religious outlook which is tied to their belief in the afterlife, death as termination of experiences or extinction, death and its impact on others with emphasis on loss, uncertainty regarding death, the inevitability of death, death as a relief and favorable condition, and the finality and irreversibility of death. The participants also claim that they do not have fears on death. Lastly, they have realistic view of the dying process but it is coupled with other wordly beliefs.